English skills with readings - Langan, John (McGraw-Hill, 2002)
One of the most comprehensive and well-respected books of its kind, this best-selling rhetoric/reader/handbook is designed for developmental writing courses that focus on paragraph writing skills in preparation for essay writing. English Skills with Readings features John Langan's crystal-clear explanations and his wide range of motivating activities and writing assingments that effectively reinforce the Four Bases of Effective Writing: Unity, Support, Coherence, and Sentence Skills. This Fifth Edition includes new coverage on using the computer, expanded coverage on the writng process, updated coverage on library resources, and fresh new examples, writing activities, editing tests, and readings.